Trastorno por déficit de atención e hiperactividad (TDAH) - Garret D. Evans; Heidi Liss Radunovich (EDIS)
This 4-page fact sheet is the Spanish-language version of FCS2134/FY001: Attention-Deficit/Hyperactivity Disorder (ADHD). Written by Garret D. Evans and Heidi Liss Radunovich and published by the UF Department of Family Youth and Community Sciences, June 2011.